Effects of music exposure during pregnancy on maternal behavior in mother rats - Yurika Takano; Masakazu Umezawa; Natsuko Kubota; Ken Takeda; Shinya Yanagita (Heliyon, 2022)
Several studies have demonstrated the possibility of positive effects of exposure to music during pregnancy on mental function in humans and animals. Although there remains a core belief in the positive effects of music during pregnancy, the underlying neurobehavioral mechanisms of these effects remain unknown. In this study, we aimed to clarify the relationship between maternal nurturing behavior and the oxytocinergic system to elucidate the effect of music on mental health during pregnancy in an experimental investigation using animal models. Pregnant rats were exposed to Mozart sonatas, and their nurturing behavior after delivery was assessed using behavioral analyses. The neural activities of the oxytocinergic system, which are associated with nurturing behavior, were investigated using FosB immunohistochemistry. Music during pregnancy significantly increased the licking behavior of mothers towards pups, which is representative of positive nurturing behavior. In contrast, this alteration in maternal behavior was shown to have no marked effect on the structure or activity of the oxytocinergic system. This study provided possible evidence that exposure to music during pregnancy had a positive effect on postnatal maternal behavior. The results also suggest that the oxytocinergic system, considered a strong candidate for the neural system that regulates maternal behavior, may not be associated with this behavioral change. Understanding the relationship between other neural systems, physiological responses, and nurturing behaviors will provide a more comprehensive explanation of the mechanisms by which music exposure during pregnancy has a positive effect on mental health.